Behavioral Barriers and the Socioeconomic Gap in Child Care Enrollment - Henning Hermes; Philipp Lergetporer; Frauke Peter; Simon Wiederhold (Center for Economic Studies and ifo Institute (CESifo), 2021)
Children with lower socioeconomic status (SES) tend to benefit more from early child care, but are substantially less likely to be enrolled. We study whether reducing behavioral barriers in the application process increases enrollment in child care for lower-SES children. In our RCT in Germany with highly subsidized child care (n > 600), treated families receive application information and personal assistance for applications. For lower-SES families, the treatment increases child care application rates by 21 pp and enrollment rates by 16 pp. Higher-SES families are not affected by the treatment. Thus, alleviating behavioral barriers closes half of the SES gap in early child care enrollment.
Keywords: I21; J13; J18; J24; C93; 330; child care; early childhood; behavioral barriers; information; educational inequality; randomized controlled trial